Pharmacological clearance of misfolded rhodopsin for the treatment of RHO‐associated retinitis pigmentosa. Issue 8 (14th June 2020) - Liu, Xujie; Feng, Bing; Vats, Abhishek; Tang, Hong; Seibel, William; Swaroop, Manju; Tawa, Gregory; Zheng, Wei; Byrne, Leah; Schurdak, Mark; Chen, Yuanyuan
Abstract: Rhodopsin mutation and misfolding is a common cause of autosomal dominant retinitis pigmentosa (RP). Using a luciferase reporter assay, we undertook a small‐molecule high‐throughput screening (HTS) of 68, 979 compounds and identified nine compounds that selectively reduced the misfolded P23H rhodopsin without an effect on the wild type (WT) rhodopsin protein. Further, we found five of these compounds, including methotrexate (MTX), promoted P23H rhodopsin degradation that also cleared out other misfolded rhodopsin mutant proteins. We showed MTX increased P23H rhodopsin degradation via the lysosomal but not the proteasomal pathway. Importantly, one intravitreal injection (IVI) of 25 pmol MTX increased electroretinogram (ERG) response and rhodopsin level in the retinae of Rho P23H/+ knock‐in mice at 1 month of age. Additionally, four weekly IVIs increased the photoreceptor cell number in the retinae of Rho P23H/+ mice compared to vehicle control. Our study indicates a therapeutic potential of repurposing MTX for the treatment of rhodopsin‐associated RP.